METHODS OF BIOMETRICAL DIAGNOSTICS IN TRANSVERSAL DIRECTION IN PATIENTS WITH MESOGNATHIC TYPE OF DENTAL ARCHES - D. A. DOMENYUK; S. V. DMITRIENKO; E. G. VEDESHINA; S. I. RISOVANNY; M. P. PORFYRIADIS; G. M.-A. BUDAYCHIEV (Кубанский научный медицинский вестник, 2017)
Aim. A comparative analysis of the horizontal parameters of mesognathic dental arches by the method of Pont and Linder-Harth. Materials and methods. The materials of the research were the results of measurements of diagnostic gypsum models of dental rows of 117 people aged 18-25 with a complete set of permanent teeth, physiological occlusion, mesognathic type of dental arches and various types of dental system. Measurement and calculation of the parameters of the dental arches in the transversal direction were carried out using the methods of Pont and Linder-Harth. Gnathic variants (mesognathy, dolichognathy, brachygnathy) of dental arches (Dmitrienko S.V., 2015) were determined taking into account the dental index calculated as the ratio of the half sum of the width of the crowns of 14 teeth to the width of the dental arch between the second molars. The types of the dental system (normodontia, macrodontia, microdontia) were determined from the summation of the width of the crowns of the upper teeth. Results. Biometric diagnostics of 117 pairs of gypsum models of dentition made it possible to establish that the methods of Pont and Linder-Harth are acceptable for the study of mesognathic dental arches as an estimate of transverse dimensions. There was no significant difference between the calculated indices and actual sizes in patients with mesognathic dental arches and various types of dental system, both in the premolar region and in the molar region. The size of the teeth is of decisive importance for the evaluation of the width of the dental arches of the mesognathic type. Conclusion. Optimization of medical and diagnostic measures in the clinic of orthodontics and orthopedic dentistry in the management of adult patients with dental-jaw pathology provides for the improvement of anthropometric studies, as well as the advisability of reviewing the conventional diagnostic regimens when studying the shape and size of dental arches to predict positive long-term results. Mathematically derived dependences of dental types of dental arches from their transversal parameters are informative, diagnostically significant values that can be used to predict the shape and size of dental arches in the treatment of patients with dentoalveolar anomalies in order to achieve an optimal functional and aesthetic result. The use of the Pont and Linder-Harth method in the analysis of the mesognathic dental arches has no significant errors, and can be used at the stages of diagnosis of shape and size anomalies in the transverse direction.